About the Problems of Teaching History to Non-History Students - S. I. Kushnir; O. Yu. Yilchenko (Высшее образование в России)
The article addresses the issues of teaching the discipline “History” to non-historical specialties. The main problems are: low interest among a sizable number of students, as well as disregarding the peculiarities of students’ specialization in preparation for classes, difficulties related to the formation of assessment toolkits for the discipline. Most of the tasks look like the unified state exam options. The authors propose a solution to these problems which is in line with the competence-based approach to teaching the discipline. The authors believe that outdated stereotypes and attitudes prevailing in the preparation to classes impede improving the methods of teaching the discipline. To ensure the continuity of the levels of education, further development of knowledge and skills acquired at school, the formation or maintenance of interest in the discipline, as well as to future professional activities, it is required to familiarize teachers with the results of the unified state exam and teaching materials on history. The authors offer certain types of tasks that aim at achieving the goals of the competence approach, among them are the tasks on knowledge of historical facts, the ability to work with historical sources, but, most importantly - the ability to identify and formulate causal relationships, as well as to formulate and defend one's own position.